Effectiveness of health promotion in preventing tobacco use among adolescents in India: Research evidence informs National Tobacco Control Programme in India - Arora, Monika (2011)
This case study has two aims. First, it describes intervention strategies from two school-based programs (HRIDAY-CATCH and Project MYTRI) designed to prevent tobacco use among adolescents in India. Second, it explains how evidence from randomized controlled trials of these intervention programs was used by HRIDAY(Health Related Information Dissemination Amongst Youth), a local non-governmental organization in Delhi, to advocate for scaling up the Government of India’s(GOI) tobacco control efforts to include school health interventions as one component of India’s National Tobacco Control Program (NTCP).